EFL Teachers Cognition and Practices of Higher Order Thinking Skill in the Indonesian Context - Ima Rahmah Hanifah; Sri Setyarini; Rojab Siti Rodliyah (Budapest International Research and Critics University, 2022)
Since teacher’s cognition of Higher Order Thinking Skills (HOTS) is one of the factors which determines the students’ HOTS, teachers’ cognitions may predispose in English language teaching practices. Teacher’s cognition has been a determining variable in a triumph of teaching practice for it holds essential roles in shaping the students’ cognition and skills. Moreover, HOTS teaching can assist the students to respond to the 21-st century challenges that require the students to think critically, being creative and innovative, communicate well, being collaborative, and confident. Teachers’ cognition and practices of higher order thinking skills in English language teaching explored in this research. Two EFL teachers from vocational high schools in West Java participated in classroom observations and a semi-structured interview. Meanwhile, document analysis also employed to triangulate the data. This research employed descriptive qualitative since it aimed to investigate the teachers’ cognition and practices of higher order thinking skills that needed qualitative insights. This study revealed that the EFL teachers’ knowledge derived from Bloom’s taxonomy revised theoretical framework. They shared the same belief in teaching HOTS in English to students. And they had positive thought toward HOTS. They practiced different methods in teaching HOTS in the classroom based on their cognition, even though there was still found incongruency between their cognition of HOTS and teaching practices due to contextual factors.